2016
DOI: 10.1097/mnh.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Claudins and mineral metabolism

Abstract: Purpose of review The tight junction (TJ) conductance made of the claudin based paracellular channel is important in the regulation of calcium and magnesium reabsorption in the kidney. This review describes recent findings of the structure, the function, and the physiologic regulation of claudin-14, claudin-16 and claudin-19 channels that through protein interactions confer calcium and magnesium permeability to the TJ. Recent findings Mutations in two TJ genes – claudin-16 and claudin-19 cause the inherited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…The CLDN16 gene has also been associated with renal hypomagnesemia. It has been proposed that claudin-16 (encoded by CLDN16 gene) is involved in controlling magnesium and calcium permeability of the paracellular pathway in the cTAL [6,21]. Several known intronic mutations in HNF1B and CLDN16 genes were found in our patient.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The CLDN16 gene has also been associated with renal hypomagnesemia. It has been proposed that claudin-16 (encoded by CLDN16 gene) is involved in controlling magnesium and calcium permeability of the paracellular pathway in the cTAL [6,21]. Several known intronic mutations in HNF1B and CLDN16 genes were found in our patient.…”
Section: Discussionmentioning
confidence: 59%
“…Schlingmann et al [16] reported 23 different mutations in TRPM6 gene among a cohort of 21 families with 28 affected individuals. Nine of these were frame shift mutations in exons 6,11,16,17,21,22,23 and 25-27. It is interesting that two patients of Pakistani ancestry with consanguinity in this cohort had homozygous deletion of exons 25-27.…”
Section: Discussionmentioning
confidence: 99%
“…The TAL is responsible for the bulk of renal Mg 2+ reabsorption 9 . In the TAL, paracellular Mg 2+ and Ca 2+ reabsorption is regulated by the Cldn14/16/19 complex 44,45 . Cldn14 mRNA expression is strongly regulated by dietary Ca 2+ intake 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity of the paracellular pathway is determined by claudins which form a cation -selective tight junction through which the Mg paracellular transport is done 23,24 . Three claudin proteins, claudin -14, claudin -16 and claudin -19, make the cation -selective paracellular pathway for Ca and Mg. Claudin -16 and claudin -19 form the pores and claudin -14 inhibits the cation selectivity of that pore 25,26 .…”
Section: Physiology Of Magnesiummentioning
confidence: 99%